Explosive Power and Its Relationship with Certain Physiological Variables and Technical Performance of Long Serve Accuracy and Defensive Blocking Skills in Volleyball - Ahmed Wlhan; Mohammed Rashid Latif; Jamal Mohammed Shuaib (Eximia, 2025)
The aim of this research was to examine explosive power and its relationship with certain physiological variables and the technical performance of the long serve accuracy and defensive blocking skills in volleyball. It also sought to determine the nature of the relationship between explosive power and these variables. The researchers employed the descriptive method using correlational analysis, as it was deemed appropriate for addressing the research problem. The study sample consisted of (12) players from the volleyball team of the College of Physical Education and Sports Sciences at the University of Diyala. The researchers utilized appropriate tools, instruments, and devices, and conducted a pilot study followed by the main performance tests relevant to the research. After data collection and statistical analysis, the findings were presented, analyzed, and discussed. The researchers reached the following conclusions: The sample demonstrated explosive power levels that were consistent with their physiological status, as measured by resting heart rate and blood lactate concentration. The sample also showed an appropriate level of explosive power in line with the technical performance of the long serve accuracy and defensive blocking skills. Emphasis should be placed on improving explosive power in both upper and lower limb muscles, as this contributes to enhancing both physical and physiological readiness, as well as skill performance in volleyball. Recommendations: The development of explosive power in the arm and leg muscles should be prioritized to align with the demands of technical performance in volleyball. The tests used in this study should be incorporated into training programs. Further similar studies should be conducted on different samples to expand the scope of research in this area.